2017
DOI: 10.3389/fenvs.2017.00012
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Nanomaterials with Plants: What Do We Need for Real Applications in Agriculture?

Abstract: The number of published researching works related with applications of nanomaterials in agriculture is increasing every year. Most of such works focus on the synthesis of nanodevices, their characteristics as nanocarriers for controlled release of active substances, and their interaction (either positive or negative) with plants or microorganisms under controlled conditions. Important knowledge has been gained about the uptake and distribution of nanomaterials in plants, although there are still gaps regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
208
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 464 publications
(212 citation statements)
references
References 54 publications
3
208
0
1
Order By: Relevance
“…Prior work has focused on studying DNA nanostructure internalization in mammalian cells, and has revealed that nanostructure size, shape, charge, and stiffness or compactness can influence the cellular internalization and uptake pathway (34,51,53,54). Analogous work in plant systems is lacking, where a few studies have reported the biolistic or passive uptake, translocation, or localization of engineered nanoparticles (carbon nanotubes, SiO 2 , quantum dots, TiO 2 NPs) to plants (13,14,28,32,33,55), while DNA nanostructure use in plants remains unexplored. Orthogonally, gene silencing through the introduction of siRNA has become a broadly-adopted tool to inactivate gene expression, to probe biosynthetic pathways, and to serve as exogenous regulators of developmental and physiological phenotypes in plants (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has focused on studying DNA nanostructure internalization in mammalian cells, and has revealed that nanostructure size, shape, charge, and stiffness or compactness can influence the cellular internalization and uptake pathway (34,51,53,54). Analogous work in plant systems is lacking, where a few studies have reported the biolistic or passive uptake, translocation, or localization of engineered nanoparticles (carbon nanotubes, SiO 2 , quantum dots, TiO 2 NPs) to plants (13,14,28,32,33,55), while DNA nanostructure use in plants remains unexplored. Orthogonally, gene silencing through the introduction of siRNA has become a broadly-adopted tool to inactivate gene expression, to probe biosynthetic pathways, and to serve as exogenous regulators of developmental and physiological phenotypes in plants (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that the NPs can easily penetrate the cell wall to release the proteins in situ , which facilitates protein–receptor interactions. Several previous reports revealed that some NPs can enter plant tissue through foliar stoma or root absorption …”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports revealed that some NPs can enter plant tissue through foliar stoma or root absorption. [32][33][34][35] The wheat seeds treated with P@NPs showed positive effects on seed vigor index [ Fig. 3(b)].…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, an ideal nanodevice for use in agricultural should comprise the following traits: (i) it should be non‐toxic and environmentally safe, to avoid further contamination problems and a negative perception on the part of consumers; (ii) its synthesis and production must be easily up‐scaled; (iii) it should involve low‐cost materials, so that the cost of the new nanoformulated products does not exceed that of the current agrochemicals and they are affordable to farmers …”
Section: Toxicity and Environmental Impactmentioning
confidence: 99%
“…96 In general terms, an ideal nanodevice for use in agricultural should comprise the following traits: (i) it should be non-toxic and environmentally safe, to avoid further contamination problems and a negative perception on the part of consumers; (ii) its synthesis and production must be easily up-scaled; (iii) it should involve low-cost materials, so that the cost of the new nanoformulated products does not exceed that of the current agrochemicals and they are affordable to farmers. 97 In order to clarify the needs and achieve conformity among procedures, the EFSA has very recently prepared a guidance statement concerning risk assessment of nanoscience, nanoobjects and nanotechnology applications in the food and feed chain for humans and animals. The document provides insights into the physicochemical properties and into exposure assessment and hazard characterisation of nanomaterials, suggesting ways to establish whether a material is indeed a nanomaterial, and establishing the key parameters to be measured and the techniques for characterisation of nanomaterials.…”
Section: Toxicity and Environmental Impactmentioning
confidence: 99%